Development of Chili Grinding Machine with Hybrid System of Wind and Solar Energy - Ameer Uddin; Zetya Maulanal Haqqy; Sulistiyanto Sulistiyanto (Journal of Electrical Engineering and Computer)
This study aims to develop an efficient chili grinding machine that utilizes a hybrid system combining wind and solar energy as a sustainable solution to address the issue of dependence on conventional energy sources, which are often expensive, environmentally unfriendly, and limited in rural areas. The main challenge is how to provide a grinding machine that can operate independently in regions with limited electricity access and high energy costs. The primary objective of this research is to design a machine capable of providing reliable power in these areas. The research involved the design and assembly of a prototype, integrating wind and solar power systems to drive a DC motor for grinding chilies. Testing was conducted to measure the power output from each energy source, with results showing that the wind turbine generates an average power of 6.715 mW, while the photovoltaic (PV) system produces an average power of 14.77 W. Combined, these sources yield a total average power output of 16.466 W. However, observations revealed that the battery charging time was longer than the operational duration of the DC motor. This hybrid-powered chili grinding machine provides a practical application of renewable energy technology, particularly suited for rural areas, and supports broader efforts to reduce carbon emissions.